Morphology of Ethylene/1-Octene Copolymers and Their Blends with High Density Polythylene: A Microscopic Evaluation - Adhikari, Rameshwar (Journal of Nepal Chemical Society, 2013)
The investigation into morphology formation in ethylene/1-octene copolymers (EOCs) comprising variable 1-octene content and their blends with high density polyethylene (HDPE) and hence their tensile mechanical properties have been reported. The morphological analysis by means of atomic force microscopy (AFM), transmission electron microscopy (TEM) and scanning electron microscopy (SEM) revealed the macrophase separation of the components in the blends. In contrast to well defined spherulitic morphology and lamellar structure of the HDPE, the EOCs exhibited progressively distorted lamellar morphology with increasing 1-octene content. At high 1-octene content, the EOC samples possessed the ‘worm-like’ crystals, which resemble the ‘fringed micelles’ discussed in the literature. The blends allow a balance of mechanical properties (stiffness and toughness) over a wide range as shown by tensile stress strain behavior of the blends. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9329 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 5-12 Uploaded date: 12/16/2013